Bone mineral density after treatment for gastric cancer: Endoscopic treatment versus gastrectomy. Issue 1 (January 2018) - Noh, Hye-Mi; Yoo, Jun-Hyun; Jeong, Ji Young; Park, Yong Soon
Abstract : Abstract: Changes in bone metabolism among gastric cancer survivors have long been recognized. The aim of our study was to clarify the changes of bone mineral density (BMD) among gastric cancer survivors who underwent endoscopic resection or gastrectomy. Forty-nine patients diagnosed with tumor, node, and metastasis (TNM) stage 1 gastric cancer with pathologic confirmation, who underwent BMD measurement just before the procedure, and had no prior osteoporosis treatment, were studied. BMD was measured with dual energy x-ray absorptiometry before and after treatment. Laboratory tests were performed using fresh serum, and serum levels of alkaline phosphatase, albumin, calcium, and phosphorus were measured. We used a nested case-control design to compare groups. Of the 49 patients, 34 underwent gastrectomy and 15 underwent endoscopic treatment. There were no differences in baseline clinical characteristics, including BMD, and biochemical data between groups. The mean and median follow-up intervals for BMD measurement were 32.6 months (standard deviation, 16.5) and 31.0 months (interquartile range: 21.5, 41.0), respectively. The follow-up BMDs of the femoral neck and total hip were lower in the gastrectomy group ( P  = .010 and .011, respectively). The percentage changes in BMD for the lumbar spine, femoral neck, and total hip were −3.30%, −1.52%, and 0.40%, respectively, in the endoscopic treatment group, and −7.17%, −6.30%, and −3.49%, respectively, in the gastrectomy group. Bone loss of the lumbar spine and femoral neck were greater in the gastrectomy group ( P  = .028 and .022, respectively). BMD is lower after gastrectomy than after endoscopic treatment among early stage gastric cancer survivors.